(untitled) (Journal of Engineering, 2020)
Drip irrigation is one of the conservative irrigation techniques since it implies supplying water directly on the soil through the emitter; it can supply water and fertilizer directly into the root zone. An equation to estimate the wetted area in unsaturated soil is taking into calculating the water absorption by roots is simulated numerically using HYDRUS (2D/3D) software. In this paper, HYDRUS comprises analytical types of the estimate of different soil hydraulic properties. Used one soil type, sandy loam, with three types of crops; (corn, tomato, and sweet sorghum), different drip discharge, different initial soil moisture content was assumed, and different time durations. The relative error for the different hydraulic soil models was calculated and was compared with the model of Brooks and Corey, 1964. There was good agreement compared with different models. The Root Mean Square Error (RMSE) was (0.23) cm, while the relative error (- 1%) and (1) for modeling efficiency (EF) for wetted radius, but wetted depth was RMSE (0.99) cm, and the relative error was (4.5%), and EF was (1).